Analysis of Factors Causing Delays in Submitting Inpatient Claims to BPJS Health Verifiers at Tanjungpura University Hospital - Ayu Rizky; Irse Desy Yana; Nuruniyah Nuruniyah (LPPM STIKes Muhammadiyah Ciamis, 2025)
Background: The National Social Security System is organized through a mandatory Social Health Insurance mechanism based on Law No. 40 of 2004 concerning the National Social Security System. The goal is to fulfill the basic needs of decent public health and the protection of the Indonesian people in the insurance system. However, the journey of the program with the most BPJS patients in the hospital is a problem, there are obstacles in the hospital regarding the submission of claims, the hospital bears the risk of costs if the claim submitted is delayed or the claim is not accepted. Objective: to determine the descriptive causes of the return of BPJS health claim files for inpatients in terms of claim submission requirements. Methods: Descriptive qualitative research using case studies where researchers explore a particular phenomenon (case) in a time and activity (program, event, process, institution or social group), collecting detailed and in-depth information using various data collection procedures during a certain period. Results: Some of the factors causing delays in claims are differences in coding perceptions by casmix officers, incorrect reading of diagnoses and medical records, less casemix officers as verifiers of internal claims in hospitals, regulations from health bpjs regarding disbursement of claims according to the MOU per month if it does not reach then the claim is postponed in the month of giving.